Identifying Elements for a Successful Approach to Applying Projects - Urska Vidmar; Tina Vukasovic (International School for Social and Business Studies, 2018)
This paper presents elements for a successful approach to addressing Horizon 2020. Horizon 2020 is the EU programme offering funding for research and innovation projects. Investing in such projects in turn secures a smart, sustainable and inclusive economic growth. The programme covers all the stages, from basic research to market penetration, and has a total value of slightly over EUR 70 billion. The investment instrument's main goals are strengthening Europe's global competitiveness, making it the best in the world-class science, eliminating obstacles that hinder innovations to get quickly in the market and changing the way in which the public and private sectors work together. Despite the fact that the program has a simple structure and requires less red tape then its predecessor (the Seventh Framework Programme - FP7), the applicants still face a lot of challenges when applying with their projects. The paper's aim is to address these challenges and to offer solutions. Primary data were collected by using the technique of surveying by e-mail. We carried out the survey by sending the e-mail to Slovene recipients of funds for Horizon 2020 and, subsequently, to Italian ones. The quantitative research results indicated that the application's success in Horizon 2020 is largely influenced by the financial projection, the knowledge of EU policies, the proposal design, as well as the proposal elements - contents, importance of the process of individual proposal elements, past experiences, partner organization, referrals and coordinators.